Best Praktice Projek Penguatan Profil Pelajar Pancasila (P5) di Sekolah Penggerak - Zainudin, Ali; Panjaitan, Ahmad Ghozali; Badrudin (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This study investigates the implementation and effectiveness of developing students' critical and innovative attitudes and integrating Pancasila values in the curriculum of SDN 244 Guruminda Bandung City. The research was conducted using descriptive qualitative approach, collecting data through observation, interview, and document analysis. The results showed that this school has successfully integrated Pancasila values in its curriculum by using a holistic and comprehensive approach. Teachers are specially trained in developing lessons that prioritize Pancasila values in every subject and extracurricular activity. In addition, the development of students' critical and innovative attitudes at SDN 244 Guruminda is encouraged through collaborative projects and active learning methods, which help students to not only understand but also apply Pancasila values in daily life and social situations. Despite facing several challenges such as limited resources, the school continues to strive to improve the quality of education by involving various stakeholders and optimizing existing facilities. The implication of this study is the importance of character education based on Pancasila values in shaping young generations who have moral integrity, social skills, and readiness to face global challenges in the future.